Penggunaan Geocell Sebagai Stabilisasi Tanah Dasar Yang Lunak Pada Proyek Pembangunan Infrastruktur Jalan Untuk Konektivitas Menuju Ibu Kota Negara (IKN) - Setiawan, Andre; Akbar, Aulia (Sultra Civil Engineering Journal (SCiEJ), 2025)
The effectiveness of using geocells as a method of stabilizing soft soil in the road construction project to the National Capital City (IKN), most of which is peat with low bearing capacity and is susceptible to subsidence and freezing. Geocells are geosynthetic materials in the form of three-dimensional cellular structures that can strengthen the soil by distributing the load evenly and resisting soil movement. This study examines the working mechanism of geocells, the characteristics of soft soil, and the application of geocells in increasing the strength, stability, and service life of road infrastructure. The research methods include literature observation, analysis of physical-mechanical parameters of soil and geocells, and evaluation of the performance of the base layer of the road reinforced with geocells through case studies and field data. The results show that the use of geocells can increase the structural stiffness of the base layer, reduce land subsidence significantly, and allow a reduction in the thickness of the granular layer by up to 50%, thereby reducing construction costs and accelerating implementation time.